2020
DOI: 10.1016/j.athoracsur.2019.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding After Cardiac Surgery Is Associated With an Increase in the Total Cost of the Hospital Stay

Abstract: Background. Cardiac surgery results in complications for some patients that lead to a longer hospital stay and higher costs. This study identified the presurgery characteristics of patients that were associated with the cost of their hospital stay and estimated how much of that cost could be attributed to a bleeding event, defined as requiring 3 units or more of packed red blood cells or returning to the operating room for bleeding. We also identified the presurgery characteristics that were associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Postoperative bleeding following cardiothoracic procedures remains an important concern with multiple avenues of investigation continuing to assess factors predisposing and potentially influencing the severity of this adverse event. Recent areas of interest include: development of new antifibrinolytic agents to reduce bleeding; 31 measurement of platelet function to reduce bleeding and mortality; 32 single or dual agent antiplatelet therapy to maximize bypass graft patency, but increase postoperative bleeding; 33 36 direct linkage of postoperative cardiac surgical bleeding with increased cost; 4 , 5 safe and efficacious use of postoperative fibrinogen concentrates; 37 , 38 role of patient blood management in reducing blood product transfusion and improving cardiac surgical outcomes; 39 , 40 transfusion reductions associated with the use of prothrombin complex concentrate; 41 , 42 morbidity associated with reoperation for bleeding following cardiac surgery; 3 , 43 , 44 methods of employing thromboelastometry (ROTEM) during cardiac surgery; 45 , 46 contribution of albumin/gelatin to postoperative bleeding; 47 49 advantages of anticoagulation management using thromboelastography (TEG) during cardiopulmonary bypass; 50 52 benefit of thrombin inhibitors for pediatric VAD anticoagulation; 53 , 54 reduction of postoperative blood loss using Unilastin as an antifibrinolytic agent; 55 , 56 and blood loss leading to multisystem organ failure and hematologic complications following LVAD insertion. 7 , 57 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative bleeding following cardiothoracic procedures remains an important concern with multiple avenues of investigation continuing to assess factors predisposing and potentially influencing the severity of this adverse event. Recent areas of interest include: development of new antifibrinolytic agents to reduce bleeding; 31 measurement of platelet function to reduce bleeding and mortality; 32 single or dual agent antiplatelet therapy to maximize bypass graft patency, but increase postoperative bleeding; 33 36 direct linkage of postoperative cardiac surgical bleeding with increased cost; 4 , 5 safe and efficacious use of postoperative fibrinogen concentrates; 37 , 38 role of patient blood management in reducing blood product transfusion and improving cardiac surgical outcomes; 39 , 40 transfusion reductions associated with the use of prothrombin complex concentrate; 41 , 42 morbidity associated with reoperation for bleeding following cardiac surgery; 3 , 43 , 44 methods of employing thromboelastometry (ROTEM) during cardiac surgery; 45 , 46 contribution of albumin/gelatin to postoperative bleeding; 47 49 advantages of anticoagulation management using thromboelastography (TEG) during cardiopulmonary bypass; 50 52 benefit of thrombin inhibitors for pediatric VAD anticoagulation; 53 , 54 reduction of postoperative blood loss using Unilastin as an antifibrinolytic agent; 55 , 56 and blood loss leading to multisystem organ failure and hematologic complications following LVAD insertion. 7 , 57 …”
Section: Discussionmentioning
confidence: 99%
“… 1 Thus, the risk of bleeding in complex cardiothoracic surgery remains clinically significant and can contribute to: exposure to blood product transfusions; 2 need for re-explorations for bleeding, 3 prolonged lengths of intensive care unit and hospital of stay; 3 increased morbidity and mortality; 3 and larger hospital costs. 4 , 5 Greater patient acuity and procedural complexity as characterized by the emerging use of aggressive antiplatelet therapy 6 and the placement of mechanical assist devices (MCAD) 7 may also contribute to increased risk of postoperative bleeding. In challenging surgical settings, hemostatic agents can be useful adjuncts to the armamentarium available to surgeons for the control of bleeding 8 12 and are known to be useful during cardiothoracic surgical operations.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In addition to this, several studies reported that major bleeding after cardiac surgery was associated with increased hospital costs. 517 Transfusion itself has undesirable effects such as immunosuppression, febrile reactions, infections, and renal and respiratory complications. Moreover, higher transfusion rates are found to be associated with low cardiac output syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…24 Moreover, perioperative bleeding can cause higher amount of blood product usage, prolonged ventilation support, extended period of intensive care stay, and loss of hospital resources. 5…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for variability in perioperative hemostasis are not known, although certain patient and surgical characteristics, including prior history of cardiac surgery, underlying bleeding diathesis, emergent surgery, and cardiopulmonary bypass (CPB) duration, have been associated with increased peri-and postoperative bleeding. 1,2 Despite often uncertain causes of persistent perioperative bleeding, even with usual resuscitative efforts, practitioners frequently turn to purified coagulation factor concentrates to enhance hemostasis. These include three-or four-factor prothrombin complex concentrates (3F-PCC or 4F-PCC), 3,4 recombinant activated factor VII (rVIIa) (NovoSeven), 4,5 and, as described by O'Donnell et al in this issue of the Journal of Cardiothoracic and Vascular Anesthesia, activated prothrombin complex concentrates, 6 also known as factor 8 inhibitor bypassing agent (FEIBA).…”
mentioning
confidence: 99%